The Determinants of Human Trafficking: A US Case Study - Jac‐Kucharski, Alicja (International Migration, 2012)
Human trafficking is a global problem. In this paper, I seek to find the determinants of international human trafficking by using the US as a case study. Previous studies have drawn primarily from the migration literature, proposing hypotheses that focus on economic factors, the level of democracy and other “push” factors in the countries of origin that create incentives for individuals to migrate. However, we know that international human trafficking is an involuntary form of migration and may be influenced by additional factors. I hypothesize that factors that influence the cost–benefit calculation of the trafficker determine the volume of human trafficking, in addition to the factors that affect the size of the pool of trafficking victims. I test my theory using the negative binomial regression model. My results indicate that while income inequality within a country and poor protection of women's rights are likely to produce a specific pool of victims, it is the reduction of operational costs for the trafficker that increases the number of individuals who are trafficked.
Keywords: dept.eco